The Pharmacological Potential - Aditya Ganeshpurkar; Ajay K. Saluja (Elsevier, 2017)
The contemporary scientific community has presently recognized flavonoids to be a unique class of therapeutic molecules due to their diverse therapeutic properties. Of these, rutin, also known as vitamin P or rutoside, has been explored for a number of pharmacological effects. Tea leaves, apples, and many more possess rutin as one of the active constituents. Today, rutin has been observed for its nutraceutical effect. The present review highlights current information and health-promoting effects of rutin. Along with this, safety pharmacology issues and SAR of the same have also been discussed.